Budgetary and external imbalances relationship: a panel data diagnostic - António Afonso; Christophe Rault (European Central Bank (ECB), 2008)
We assess the cointegration relationship between current account and budget balances, and effective real exchange rates, using recent bootstrap panel cointegration techniques and SUR methods. We investigate the magnitude of the relationship between the two imbalances for each country for the period 1970-2007, and for different EU and OECD country groupings. The panel cointegration tests used allow for within and between correlation, while the SUR results show both positive and negative effects of budget balances on current account balances for several countries. The magnitude of the effects varies across countries, and there is no evidence pointing to a direct and close relationship between budgetary and current account balances.
Keywords: C23; E62; F32; H62; 330; budget balance; EU; external balance; Panel Cointegration; Haushaltsdefizit; Leistungsbilanz; Panel; Kointegration; EU-Staaten